Hepatozoon spp. em carnívoros neotropicais presentes em vida livre no Parque Nacional das Emas, em Goiás, Brasil - Metzger, Betina [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of this study was to investigate the occurrence of Hepatozoon spp. in free ranging neotropical carnivores from Brazil. 158 blood samples were analyzed from Canidae, Procyonidae and Mephitidae from Emas National Park, in the State of Goias, Brazil. From the sampling total, 75 were obtained from Chrysocyon brachyurus (maned wolf), 65 from Cerdocyon thous (crab-eating dog), 10 from Conepatus semistriatus (striped hog-nosed skunk), 06 from Lycalopex vetulus (hoary fox) and two from Nasua nasua (South American coati). Hepatozoon spp. were diagnosed by Polymerase Chain Reaction (PCR) after DNA was extracted. From the total analyzed, 63.92% samples were parasitized by Hepatozoon; and from the positive samples 41.14% were collected from C. brachyurus, 18.35% from C. thous, 3.79% from L. vetulus and 0.63% from N. nasua. The majority of C. brachyurus population (86.66%) was infected and also 44.61% of C. thous and 100% of L. vetulus studied. Molecular characterization of the isolates was performed after sequencing and phylogenetic analyses. These demonstrated that the isolates from C. thous and the majority of the ones from C. Brachyurus showed high similarity with Hepatozoon sp. from C. thous from the State of Espirito Santo and also with Hepatozoon americanum. The isolate of N. nasua showed similarity with H. felis; and the ones from L. vetulus with H. canis from domestic dog. The molecular identification of Hepatozoon sp. from N. nasua as well as the infection by this hematozoa in free ranging C. brachyurus and L. vetulus are novelties in the world

O trabalho teve como objetivo investigar a ocorrência de Hepatozoon spp. em carnívoros neotropicais de vida livre no Brasil. Foram analisadas 158 amostras sanguíneas de Canidae, Procyonidae e Mephitidae presentes no Parque Nacional das Emas, em Goiás. Do total amostral, 75 foram obtidas de Chrysocyon brachyurus (lobo-guará), 65 de Cerdocyon thous (cachorro do mato), 10 de Conepatus semistriatus (jaratataca), 06 de Lycalopex vetulus (raposinha do campo) e dois de Nasua nasua (quati). O diagnóstico de Hepatozoon spp. foi feito através da Reação em Cadeia de Polimerase (PCR) após a extração de DNA. Do total analisado, 63,92% das amostras estavam parasitadas por Hepatozoon, sendo que deste total, 41,14% eram provenientes de C. brachyurus, 18,35% de C. thous, 3,79% de L. vetulus e 0,63% de N. nasua. A maioria da população de C. brachyurus (86,66%) apresentou-se infectada, assim como 44,61% dos exemplares de C. thous e 100% dos L. vetulus estudados. A caracterização molecular dos isolados obtidos foi feita após o sequenciamento e a análise filogenética. Essa última demonstrou que isolados sequenciados de C. thous e a maioria dos de C. Brachyurus apresentaram alta similaridade com Hepatozoon sp. isolado de C. thous no Espirito Santo e também com Hepatozoon americanum. O isolado de N. nasua apresentou similaridade com H. felis e os de L. vetulus com Hepatozoon canis em cão doméstico. A identificação molecular de Hepatozoon sp. em N. nasua e os relatos das infecções por este hematozoário em C. brachyurus e em L. vetulus de vida livre são inéditos no mundo
Keywords: Animais carnívoros; Parasito; Protozoario; Leucócitos; Carnivora